2021
DOI: 10.1002/cnr2.1370
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized omental lymphatic transplant for upper extremity lymphedema: A systematic review

Abstract: Background: Vascularized omental lymphatic transplant (VOLT) is an increasingly popular treatment of extremity lymphedema given its promising donor site. While the success of VOLT in the treatment of lymphedema has been reported previously, several questions remain.Aim: To further elucidate appropriate use of VOLT in the treatment of lymphedema, specifically addressing patient selection, harvest technique, and operative methods.Methods and Results: A systematic review of VOLT for upper extremity lymphedema was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The appearance subdomain scores remained relatively constant in patients with fat-dominant disease, possibly because individuals in this cohort likely experienced a dramatic change in their limb volumes following debulking, leading to a major improvement in their perceived appearance that would have occurred prior to VLNT. Overall, the findings from the current study are in concordance with other studies that have reported positive effects of VLNT on patient quality of life [ 10 , 35 , 36 ] . However, in the current study, the beneficial effects may be less directly related to changes in limb volumes and may be more heavily influenced by the reduction in time spent wearing compression garments.…”
Section: Discussionsupporting
confidence: 92%
“…The appearance subdomain scores remained relatively constant in patients with fat-dominant disease, possibly because individuals in this cohort likely experienced a dramatic change in their limb volumes following debulking, leading to a major improvement in their perceived appearance that would have occurred prior to VLNT. Overall, the findings from the current study are in concordance with other studies that have reported positive effects of VLNT on patient quality of life [ 10 , 35 , 36 ] . However, in the current study, the beneficial effects may be less directly related to changes in limb volumes and may be more heavily influenced by the reduction in time spent wearing compression garments.…”
Section: Discussionsupporting
confidence: 92%
“…In our case, omental flap transfer resulted in a significant reduction in infection, resolution of the wound, and a gradual decrease in limb volume over 5 years of follow-up. The vascularized omentum transfers contain lymphoreticular bodies known as milky spots, 5 which drain fluid from the interstitial space 6 The omentum possesses immunologic and angiogenesis capabilities as well. Forte et al 7 noticed a 30%–70% volume reduction within 0.5–4 years.…”
Section: Discussionmentioning
confidence: 99%
“…showing that the vascularized omental lymphatic transfer is safe and efficacious (Jarvis et al, 2021;Schaverien et al, 2021). In addition to minimizing the morbidity of the laparotomy through laparoscopic harvesting techniques, there is no risk of donor site lymphedema, and there is increased availability of lymph node tissue (Nguyen & Suami, 2015).…”
Section: T a B L E 1 Patient Demographics And Surgical Detailsmentioning
confidence: 99%
“…There has been a shift towards implementing surgical intervention earlier, attempting to stop the progression of disease leading to permanent fibrosis, with VLNTs becoming more popular (Jarvis et al, 2021; Raju & Chang, 2015). Different VLNTs have been described including inguinal, gastroepiploic, thoracic, supraclavicular, submental and omental (Cheng et al, 2012; Jarvis et al, 2021; Raju & Chang, 2015). Of these, the omental vascularized lymph node transfer has gained interest as of late due to its success at treatment of upper extremity lymphedema and decreased risk of donor‐site lymphedema compared to other recipient sites (Forte et al, 2019; Jarvis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation